Lean models, complex realities: elite interactions in post-conflict democratisation at the local level. Issue 4 (4th July 2018) - Groß, Lisa
Abstract: This article argues that accounting for the complexity of interaction in post-conflict democracy promotion is important to understand how interactions influence post-conflict democratisation. Using the case of democracy promotion in Kosovo, the article uncovers two aspects in interaction processes where accounting for complexity is particularly useful: domestic goals and actor constellations. Taking into account the variety of domestic goals helps to understand how democratic reforms are subverted by domestic elites for the sake of their own domestic agenda. Disentangling the complexity of actor constellations demonstrates that interaction dynamics are shaped by the leverage and the number of international actors involved in the negotiation. The article draws on fine-grained local-level data from Kosovo to illustrate the argument.